Tinjauan Yuridis Terhadap Pengelolaan Hutan Oleh Masyarakat Di Kawasan Geopark Rinjani: (Studi Di Hutan Benang Kelambu Lombok Tengah) - Khairuddin Khairuddin; M. Yazid Fathoni (Fakultas Hukum Universitas Mataram, 2023)
This study aims to find out the legal basis for communities that carry out forest management in the Rinjani Geopark area and how the government plays a role in supervising community actions on forest management in the Rinjani Geopark area, especially in the Benang Kelambu forest area. This type of research is empirical legal research, with a statutory approach, a sociological approach and a conceptual approach. The results of this study show that (1) the legal basis for the community to manage, namely forests, refers to the Decree (SK) of the Minister of Forestry No. 436 / Menhut-II / 07 concerning the Determination of Community Forest Work Areas and is strengthened by the rules that legalize these activities. (2) The role of the government in forest management is: the role to control, manage, regulate and play a role to supervise so that forest sustainability can be maintained properly.